Household Headship and Infant Mortality in India: Evaluating the Determinants and Differentials - Ashish Kumar Gupta, M Phil; Kakoli Borkotoky, M Phil; Amit Kumar, M Phi (Global Health and Education Projects, Inc., 2014)
Background: There has been ample discussion on the levels and trends of infant mortality in India over time, but what remains less explored are the differentials in infant mortality according to household headship. This paper examined the differences in the determinants of infant mortality between male-headed households (MHH) and female-headed households (FHH). Methods: The study used Cox proportional hazard model to examine the determinants of infant death, and Kaplan-Meier estimation technique to examine the survival pattern during infancy using data from Indian National Family Health Survey (2005-06). The analysis is restricted to women who had at least one live birth in the five years preceding the survey. Results: The study observed that household size and number of children below five are significant risk factors of infant mortality in MHH while length of previous birth interval is the only significant risk factor of infant death in FHH. Conclusions and Global Health Implications: The results indicate that children from FHH have higher survival probability at each age than children from MHH irrespective of place of residence and sex of the child.